Polymodal faulting in rifting settings: strain field and role of pre-existing structures - Collanega, Luca (Università degli studi di Padova, 2018)
Normal faults have been typically thought to develop sub-perpendicularly to the extension direction, forming systems of sub-parallel faults. However, a variety of processes may result in the simultaneous development of faults with different strikes (i.e. polymodal faulting), most notably 3D strain fields and influence of pre-existing fabrics. Whilst the classic model on faulting suggests that complex fault patterns should result from polyphase deformation with different extension directions, the concept of polymodal faulting can account for the development of different fault sets under the same stress regime, having possibly a strong impact on the reconstruction of the palaeostress. In the thesis, 3D seismic data were used to assess the occurrence of polymodal faulting in two different extensional tectonic settings: the Barents Sea rift-shear margin (Paper 1), offshore northern Norway, and the Taranaki back-arc rift (Paper 3), offshore New Zealand. Then, analogue models and kinematic analysis were used to investigate the deformation processes. In both settings, polymodal faulting was observed at the 10s of kilometres scale. The occurrence of polymodal faulting at such large scale may affect the previous interpretation of the structural histories of these sedimentary basins, reducing the number of tectonic phases that should be envisaged to explain the observed structures. The tectonic setting appears to have a strong influence on the deformation processes, with polymodal faulting occurring under the control of a 3D strain field in the Barents Sea and of pre-existing basement fabrics in the Taranaki Basin. In the Barents Sea, the onset of a 3D strain field is related to the interaction between the Atlantic and the Arctic rifts, coupled with a characteristic brittle-ductile-brittle mechanical stratigraphy. The analogue models performed in this thesis (Paper 2) highlighted that in 3D strain fields, local fault interactions exert a strong control on the final fault geometries, with the faults forming perpendicular ...